Real effective exchange rate uncertainty, threshold effects, and aggregate investment: Evidence from Latin American countries - Bianca Clausen (Universität zu Köln, Institut für Wirtschaftspolitik (iwp), 2008)
This paper provides new empirical evidence on the relationship between real effective exchange rate uncertainty and aggregate investment in six Latin American economies. Its main contributions are that it explicitly tests for linear as well as non-linear effects of uncertainty in a time-series model that allows the country-specific interpretation. A (G)ARCH-based uncertainty measure is constructed for each country which is then included in a GMM time-series model that accounts for the endogeneity of the variables. When accounting for threshold effects, this paper finds that high levels of real effective exchange rate uncertainty affect aggregate investment negatively in all countries in the sample.
Keywords: F21; F31; 330; exchange rate uncertainty; GARCH; investment; threshold effects; GMM